Environmental conditions in the maintenance room and in the art store of the museum - case study - Charkowska, Anna; Hendiger, Jacek; Mijakowski, Maciej; Bartkiewicz, Piotr (Instal, 2020)
Maintaining the required relative humidity and temperature in areas where works of art are stored, exhibited, or maintained is often a common challenge for specialists in various fields and interdisciplinary teams. Combining the knowledge and experience of monument conservators and specialists in technical sciences in the field of environmental conditions, psychrometric changes of air, thermodynamics, indoor air flows, operation of ventilation and air conditioning systems, allows to solve many problems that may occur in such interesting and demanding environments as museums, archives, art magazines and conservation studios. In order to present such problems and ways of analysing them, the article refers to issues related to a ventilation and air conditioning installation working for the needs of museum rooms, serving as a maintenance room and an art store. The formulated conclusions can be used by both museum employees and engineers dealing with internal installations in museums and archives in their professional work, to analyse the correctness and correction of ventilation and air conditioning systems in order to achieve the required goal: meeting very restrictive requirements in the field of internal conditions in rooms for various purposes.